Atractus albuquerquei Cunha & Nascimento, 1983 (Serpentes, dipsadidae): First record for the state of minas gerais, southeastern Brazil - do Nascimento, Bruno Tayar Marinho [UNESP]; Maffei, Fábio [UNESP]; Moya, Guilherme Marson; Donatelli, Reginaldo José [UNESP] (Pensoft Publishers, 2017)
We present the first record of Atractus albuquerquei for the state of Minas Gerais, southeastern Brazil. This record extends the distribution of the species 500 km east of Emas National Park and 570 km south of Chapada dos Veadeiros National Park, both in the state of Goiás.
Keywords: Cerrado; Reptile; Snake; Squamata